Diegetic and nondiegetic sounds in film scoring of Pengabdi Setan film - Pandu Watu Alam; Rangga Saptya Mohamad Permana; Sri Seti Indriani (Universitas Padjadjaran, 2023)
Background: This research examines the 2017 film Pengabdi Setan scoring function. Joko Anwar wrote and directed the film Pengabdi Setan, released on September 28, 2017. This film is a remake of a 1980 film of the same name. In this film, the score is essential for visually confirming symbols or incomplete messages. There are two types of sound: diegetic sound and non-diegetic sound. Purpose: This research aims to determine how diegetic and non-diegetic sound were used to create a horror atmosphere in the film Pengabdi Setan. Methods: The authors described the audio analysis results in the form of diegetic and non-diegetic sounds using a qualitative descriptive analysis. Documented assessment and observation were employed as data collection techniques. Results: The results indicate that infrasonic sound (infrasound) and sub-bass frequencies in the form of non-diegetic sounds emotionally impact audiences. The typical frequency is 31 Hz, and although it is inaudible to the human ear, the audience can sense the vibrations of this frequency. This frequency can typically only be perceived as a “chest rumble.” In general, both diegetic and non-diegetic sounds in the film Pengabdi Setan contribute to completing the defective message symbol. The combination of infrasonic sound effects, sub-bass, and musical composition validates the visual messages or symbols. Implications: This research can theoretically serve as a resource for future researchers interested in studying diegetic and non-diegetic sound in film. Directors and cinema sound engineers can use this research to construct diegetic and non-diegetic sound in their films, particularly horror films.